Analysis of the level of financial performance of sharia commercial banks with the Islamic Performance Index approach - Dewi Kirowati; Shinta Noor Anggraeny; Lely Kumalawati (Journal of Social Science and Humanities, 2025)
The purpose of the study was to analyze the level of financial performance of sharia commercial banks in Indonesia with the Islamic Performance Index approach for the period 2021 - 2024. Because the growth of sharia commercial banks is quite rapid, it is necessary to know the level of financial performance based on sharia principles in Islam,. The type of research used is a non -statistical quantitative descriptive research with a population of 13 sharia commercial banks in Indonesia and purposive sampling sampling techniques with a sample of 4 sharia commercial banks that publish financial statements up to 2024. Employee Welfare Ratio with a very unsatisfactory predicate, the value of Islamic Investment vs. Non -Islamic Investment as a whole with a very satisfying predicate, the value of Islamic income vs non -Islamic income as a whole with a satisfactory predicate